A dynamic stochastic general equilibrium model for the peruvian Economy with a commodity sector - Chávez Vásquez, Darha Valeskka (2024)
The emerging Peruvian economy is small and open with a rele- vant commodity sector. For that reason, policy makers study how the evolution of the price of copper affects its business cycles and iden- tify the transmission channels involved. This paper relies on a New Keynesian Dynamic Stochastic General Equilibrium model1 with (i) firms that have some monopoly power and produce intermediate va- rieties of goods, (ii) firms that produce final goods for domestic and international markets, (iii) importers who retail final foreign goods to households, (iv) firms that produce capital goods and (v) one firm that produces a commodity good that is entirely sold in the international market. The aim is to describe how a commodity price shock and a commodity production shock impact the Peruvian economy. Regarding the price shock, we observe a deterioration in the net foreign asset position due to capital inflow into the commodity sector, causing real appreciation of the local currency. This increases labor demand, real wages, and domestic goods prices, leading to a decline in domestic production. Initially, this generates a drop in the output growth that is reverted due to positive and delayed effects on invest- ment. Similarly, a positive shock to copper production boosts exports. Capital inflows worsen the net foreign asset position and lower the ex- change rate. Investment in domestic and foreign goods increases as capital rises. The combined rise in investment and exports, along with the fall in imports, increases production.